Margret & H.A. Rey's Curious George goes to a movie - Margret & H.A. Rey (1906-1996); (1898-1977); Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Vipah Interactive (Boston : Houghton Mifflin, 1998)
When his curiosity leads him to investigate how the movie gets onto the screen, George, an inquisitive monkey, disrupts the show.
"Based on the character of Curious George created by Margret and H.A. Rey"--Title page verso.
Accelerated Reader
AR
Keywords: Monkeys -- Juvenile fiction; Motion picture theaters -- Juvenile fiction; Monkeys -- Fiction; Motion picture theaters -- Fiction; Humorous fiction; Picture books